(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article presents an approach to teaching English by focusing on content rather than grammar. It argues that meaningful communication and immersive content can help learners pick up the language more naturally and effectively than traditional grammar-based methods. By reviewing research and practical examples, the article shows how a content-driven approach makes learning more engaging and effective for students.